2001
DOI: 10.1111/j.1530-0277.2001.tb02391.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Relevance of Human ADH Polymorphism

Abstract: This article represents the proceedings of a symposium at the 2000 ISBRA Meeting in Yokohama, Japan. The chairs were C. J. Peter Eriksson and Tatsushige Fukunaga. The presentations were (1) 4-Methylpyrazole as a tool in the investigation of the role of ADH in the actions of alcohol in humans, by Taisto Sarkola and C. J. Peter Eriksson; (2) ADH2 polymorphism and flushing in Asian populations, by Wei (6) ADH genotypes and alcohol use in Europeans, by John B. Whitfield.T HE BULK OF human alcohol metabolism takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…The high and prolonged exposure to ethanol may partly explain the finding that individuals with ADH1B*1/*1 are at high risk of developing alcoholism, 7,8 and that alcoholics with ADH1B*1/*1 are prone to binge drinking and the withdrawal syndrome earlier in life than those with other genotypes. 39 Contrary to expectation, the ALDH2 genotype did not affect the ethanol or acetaldehyde levels of the subjects in the morning after drinking the day before. These findings also contrast with the results of alcohol challenge tests, which clearly showed very high peak acetaldehyde concentrations in the blood 9 and saliva 22 of inactive ALDH2 heterozygotes after light drinking.…”
Section: Discussioncontrasting
confidence: 40%
“…The high and prolonged exposure to ethanol may partly explain the finding that individuals with ADH1B*1/*1 are at high risk of developing alcoholism, 7,8 and that alcoholics with ADH1B*1/*1 are prone to binge drinking and the withdrawal syndrome earlier in life than those with other genotypes. 39 Contrary to expectation, the ALDH2 genotype did not affect the ethanol or acetaldehyde levels of the subjects in the morning after drinking the day before. These findings also contrast with the results of alcohol challenge tests, which clearly showed very high peak acetaldehyde concentrations in the blood 9 and saliva 22 of inactive ALDH2 heterozygotes after light drinking.…”
Section: Discussioncontrasting
confidence: 40%
“…Both ADH and ALDH are polymorphic enzymes and critical players in ethanol metabolism; ADH1B catalyzes the oxidation of ethanol to acetaldehyde, and ALDH2 catalyzes the oxidation of acetaldehyde to acetate. Functional polymorphisms in the ADH1B and ALDH2 genes (Agarwal, 2001) have a significant influence on the activities of both enzymes, and are stratified by race, with the ADH1B*2 (increased catalytic activity) and ALDH2*2 (reduced catalytic activity) alleles being common in East Asians and virtually absent in Caucasians (Eriksson et al, 2001). Theoretically, subjects with increased or rapid ADH activity may quickly metabolize GSK2251052, leading to lower parent concentrations, which in turn may impact efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The alcohol dehydrogenase 1B (ADH1B) gene (formerly called ADH2) exhibits genetic polymorphisms resulting in altered functional and catalytic properties in vitro (Agarwal, 2001). A strongly increased oxidation capability has been associated with the *2 allele (Bosron et al, 1983;Eriksson et al, 2001), an Arg47His substitution with reported allele frequencies ranging between 0 and 6.8% in Europeans (Brennan et al, 2004).…”
mentioning
confidence: 99%